Analisis Pelaksanaan Projek Penguatan Profil Pelajar Pancasila Pada Kelas V Di SDN Pelang Kidul 2 - Rahayu, Nurul Widya; Kusumastuti, Narendradewi; Khasanah, Aulia Fajar (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
This study was conducted to analyze the implementation of the Pancasila peljr profile strengthening project in class V at SDN Pelang Kidul 2. The type of research conducted is qualitative descriptive. The technique used to analyze the data is the technique of mils and Huberman. Research findings or research results that have been carried out regarding the implementation of the Pancasila student profile strengthening project have the results that, there are 3 stages carried out in the Pancasila student profile strengthening project, namely planning, at this stage the teacher does not make a project module. Implementation, at this stage student involvement is very focused so that students can understand the implementation of the project, closing, in this thap the teacher gives motivation and encouragement. Then, evaluation at this stage the teacher evaluates the implementation process carried out by the students. There are 2 factors in the implementation of the Pancasila peljar profile strengthening project, namely supporting factors and inhibiting factors.